Up-regulation of receptor interaction protein 140 promotes glucolipotoxicity-induced damage in MIN6 cells - Xue, Li Jun; Huang, Qi; Zeng, Jiao E; Zhu, Hui; Xu, Cheng Yan (Cellular and Molecular Biology, 2018)
The receptor interaction protein 140 (RIP140) cofactor is a key regulator of metabolic balance, but its function in glucose- and lipid-mediated damage in islet Î² cells is unknown and was investigated in this study. RIP140 expression and distribution was evaluated in MIN6 cells under high glucose and lipid conditions using real-time Polymerase Chain Reaction (PCR), western blotting and confocal laser scanning microscopy. Cells were separately treated with 500 Î¼M palmitic acid and 25 mM glucose when RIP140 expression was upregulated or downregulated, and cell viability, apoptosis rate, the level of oxidative stress and insulin secretion was assessed, as was the expression of related genes. Increased glucose and palmitic acid elevated RIP140 expression and distribution in nuclei. Overexpression of RIP140 promoted apoptosis but inhibited cell viability in MIN6 cells, and basal insulin secretion and glucose-stimulated insulin secretion levels were altered following treatment with glucose and palmitic acid. In addition, oxidative stress was elevated, phosphorylated extracellular signal-regulated kinases 1/2 and uncoupling protein 2 messenger RNA (mRNA) abundance were increased, B-cell lymphoma-2 protein levels were decreased, and peroxisome proliferators activated receptor gamma co-activator 1 alpha, phosphoenolpyruvate carboxykinase , and pancreatic and duodenal homeobox-1 mRNA levels were downregulated. Furthermore, glucolipotoxicity-induced damage was reversed when RIP140 expression was downregulated by small interfering RNA (SiRNA). RIP140 promotes islet Î² cells damage caused by glucolipotoxicity.